A comparative life cycle assessment of fiber-reinforced polymers as a sustainable reinforcement option in concrete beams - Sbahieh, Sami; Mckay, Gordon; Al-Ghamdi, Sami G. (Frontiers in Built Environment, 2023)
Environmental awareness and the need for sustainable construction inspired researchers and practitioners to explore innovative alternatives that might reduce greenhouse gas emissions and energy use related to excessive structural work. One such alternative is the utilization of Fiber-Reinforced Polymer (FRP) bars as a reinforcement in reinforced concrete members. FRP bars possess favorable characteristics like high tensile strength, lightweight and corrosion resistance compared to steel. This feature makes FRP bars a potential solution for utilizing seawater instead of fresh water in concrete mixtures, especially in areas facing a harsh climate and water shortage like the Arabian Peninsula. This paper aims to assess and evaluate the environmental impacts through life cycle assessment of glass fiber-reinforced polymer bars, carbon fiber-reinforced polymer, and steel glass fiber reinforced polymer bars compared to steel bars. Moreover, another LCA was conducted comparing steel-reinforced beams made with desalinated fresh water to GFRP/CFRP reinforced beams made with seawater for the concrete mixture. The results indicate that the GFRP bar performed better than the steel bar in 10 out of 14 categories, while the carbon fiber-reinforced polymer bar performed worse than the steel bar in 10 out of 14 categories. The SGFRP bar had a result between the steel and GFRP bar, outperforming the steel bar in 10 categories. Furthermore, the GFRP beam exhibited better environmental performance than the steel beam in 9 out of 14 categories, while the CFRP beam performed better than the steel beam in 8 categories, attributed to the reduction in reinforcement ratio due to the high tensile strength of CFRP and GFRP bars compared to steel bars. Overall, this study sheds light on the possible environmental advantages of using FRP bars in construction and highlights the importance of sustainable construction practices in minimizing environmental impacts.